Bacterial sensitivity pattern of neonatal early onset sepsis in a tertiary care hospital in Assam - Dr. Dipti Devi; Dr. D Sharad Gedam (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Current trend in Neonatal mortality rate (NMR) is stagnant for last few decades. Early onset sepsisis one of commonest causes of NMR. As clinical presentation is often nonspecific, a high degree of suspicion is required for early initiation of specific therapy. Choice of empiricalantibiotic is the cornerstone of specific therapy. Depending on the culture report it can be switched over to appropriate antibiotic. Prevalence of bacterial pathogen varies in different locality. So, every neonatal care set up should have a periodical review of the bacteriological profile of the locality. Method: A prospective cohort study was undertaken in the department of Pediatrics and Obstetrics of Tezpur Medical College and hospital, Assam to find out the bacteriological profile of culture proven early onset sepsis (EOS) during July 2016 to June 2017. Results: Out of 5960 hospital born babies, 298 babies fulfilled the inclusion and exclusion criteria. 15(5.03 %) babieswere with probable sepsis by clinical criteria and positive sepsis screen. Out of these, 7(46.66 %) babies were culture positive. Gram negative organisms were 85.7 % of isolates of which 3(42.8%) were Actinobacterspp followed by klebseilla, E. Coli and Pseudomonus Aeroginosa. Methicillin resistant Staph aureus was the only gram-positive organism. There was no growth of group B streptococcus. Most of the organisms were resistant to common drugs. One of Actinobacter was resistant to all drugs including meropenam. Conclusion: We conclude that only local policy of rational antibiotic use can prevent the problem of drug resistance and reduce NMR due to sepsis.